(untitled) (Archives of Mechanics - Test, 1999)
Cancellous bone with plate-like architecture is modelled as an elastic cellular solid with regular microstructure. General formulae for the effective moduli are derived. Specific examples concern plate-like cancellous bone with isotropic trabeculae.